KYJEV OR KYJIV? USE OF UKRAINIAN CITY NAMES IN SLOVAK MEDIA AS AN EXPRESSION OF SOLIDARITY - Rabina, Daniel (Communication Today, 2024)
At the time of our study, more than five hundred days had passed since the beginning of the Russian occupation of Ukraine. Given the sufficient time gap and the significant amount of media output, I can thus analyse a unique phenomenon that appeared in the Slovak media shortly after the beginning of the occupation – the appearance of previously unused variants of the names of the cities Kyjev or Kyjiv [Kyiv], Charkov or Charkiv [Kharkiv], and Ľvov or Ľviv [Lviv]. Through a quantitative analysis, we focused on media content across publishing houses N Press (Denník N), Petit Press (SME), OUR MEDIA SR (Pravda) and news portals www.tasr.sk and www.sita.sk. As a follow-up to the performed analysis, I directly confronted representatives of individual media with the findings, including ascertaining the motivations and reasons that led the editors to change, or persistence in using the original names. In the study, I also point out the phenomenon of the emerging language problem, which is already occupying the attention of linguists today.